Working Excessively and Burnout Among Nurses in the Context of Sick Leaves - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Sobolewski, Marek (Frontiers in Psychology, 2020)
Introduction: Nurses are particularly at risk of being affected by professional burnout because of the unique patient – caregiver relationship, which requires strong emotional involvement. Aim: In this study, we decided to examine the mutual correlations of working excessively and burnout – two basic occurrences affecting the mental well-being of employees – and their relationship with sick leave. Materials and methods: The study was conducted among 460 nurses working in 3 hospitals in Poland. The polish version of Maslach Burnout Inventory and the Working Excessively Questionnaire developed by Paluchowski were used to conduct the survey. All the demographic data and data on sick leaves were obtained from surveys in the form of respondents’ self-reports. Results: The constructed regression model shows that the tendency to work excessively, as assessed by loss of control over work (LCW), perfectionist work style (PWS), and perceived oppressiveness of the organization (OOP) measures, explains 12.4% of the variation in burnout levels. This confirms that overburden with work can be a factor contributing to the increase in burnout measures. The constructed logistic regression model showed that increase in the level of occupational burnout by 1 point, the chance of nurse having at least three sick leaves per year increases 1.029 times (i.e. by about 2.9%). None of working excessively measures affected the frequency of sick leaves. Conclusions: 1. Excessive workload increases burnout symptoms, which in turn encourages nurses to take sick leave more frequently. 2. The tendency for nurses to overburden themselves with work may be seen by hospital managers as a positive phenomenon, but, based on this study, it is clear that this can only be done in the short term, whereas in the long term it will be clearly detrimental to the organization of hospitals and the quality of care.